Performance analysis of gas turbine / Sharil Khalid and Hasnol Zakaria - Khalid, Sharil; Zakaria, Hasnol (2000)
This project is about studying the performance of gas turbine with the aid of a Programme that has been written in FORTRAN 77 language. By fixing the certain parameters as an input data based on thermodynamics properties, gas data, mass flow rate, rotor speed and annulus size, then the duty coefficients that is 'V (work coefficient) and (flow coefficient) and also other parameters such as dimensionless velocity triangles, Mach number and etc. can be determined. All the parameters that have been calculated are very useful during evaluating the performance of gas turbine (will be discuss in Chapter 3). As an additional, this programme is only calculating all the parameters at the mean radius. As a start we assume there is only one stage involved for convenience purposes during writing the programme.